Evaluación y experiencias en el control de conificación en pozos con alto corte de agua en yacimientos con empuje hidráulico (2018)
Oil production with high water-oil ratio (WOR) in strong water drive reservoirs are prone to generate coning in watered-out production wells. The water-oil contact (WOC) moves upwards through the open perforated intervals in the top of producer sand. Water coning problems are difficult to diagnose and to correct. An inadequate diagnosis and poor knowledge regarding the window of application of technological solutions to control water coning, have evidenced to be an important factor of the low success rate in solving this problem. This paper presents insights based on author’s expertise, for the precise diagnostics of water coning, and the most prospective technical solutions among chemicals, mechanicals and hybrids methods to date.